High-performance cellulose acetate butyrate composite material and preparation method thereof

By combining cellulose acetate butyrate with triethyl citrate and new silica hybrid nanoparticles, high-performance cellulose acetate butyrate composite materials were prepared, which solved the problem of low performance of existing materials, and achieved significant improvements in mechanical strength, ductility, ultraviolet barrier, antioxidant, antibacterial and ammonia-sensitive discoloration, and was suitable for applications in a variety of fields.

CN119798794APending Publication Date: 2025-04-11GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411956711.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-29
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing cellulose acetate butyrate materials have low mechanical strength, ductility, ultraviolet barrier, antioxidant, antibacterial and ammonia-sensitive discoloration properties, which limits their application in food packaging, smart materials, antibacterial materials, ultraviolet protection, ammonia detection, environmental monitoring and safety.

Method used

High-performance cellulose acetate butyrate composite materials were prepared by combining cellulose acetate with triethyl citrate and novel silica hybrid nanoparticles. The preparation method of novel silica hybrid nanoparticles includes blending nanosilica with ferrous sulfate heptahydrate and 4-hydroxycoumarin, and obtaining it by centrifugation, washing, and drying.

Benefits of technology

This composite material significantly improves mechanical strength, ductility, ultraviolet barrier, antioxidant, antibacterial and ammonia-sensitive discoloration properties, and is suitable for food packaging, smart materials, antibacterial materials, ultraviolet protection, ammonia detection, environmental monitoring and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798794A_ABST
    Figure CN119798794A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer composite materials, and particularly relates to a high-performance cellulose acetate butyrate composite material and a preparation method thereof. The high-performance cellulose acetate butyrate composite material is prepared from the following components in parts by weight: 100 parts of cellulose acetate butyrate, 5 parts of triethyl citrate and 2.5 to 10 parts of novel silicon dioxide hybrid nanoparticles. The high-performance cellulose acetate butyrate composite material has excellent properties and functions of mechanical strength, ductility, ultraviolet blocking, oxidation resistance, bacteria resistance, ammonia-sensitive discoloration and the like, is simple in preparation process, environment-friendly, low in cost and suitable for large-scale production, and has wide application prospects. The method has wide application value in the fields of food packaging, intelligent materials, antibacterial materials, ultraviolet protection, ammonia gas detection, environment monitoring, safety and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high-performance cellulose acetate butyrate composite material and a preparation method thereof. Background Art

[0002] Cellulose acetate butyrate, also known as cellulose acetate butyrate, is a chemically modified natural polymer produced by the mixed esterification reaction of acetic acid and butyric anhydride. It combines the characteristics of cellulose acetate and cellulose butyrate. By changing the ratio of acetic acid and butyric acid, cellulose acetate butyrate products with different properties can be prepared. Cellulose acetate butyrate not only inherits the excellent solubility of cellulose acetate, but also introduces butyrate groups to enhance its flexibility and weather resistance. It is widely used in biotechnology, food plastics industry and coating industry. However, cellulose acetate butyrate has limited mechanical strength, relatively low tensile strength and bending strength, general heat resistance, lack of ammonia-sensitive color change, antibacterial, antioxidant, UV shielding and other properties, which limits the application of cellulose acetate butyrate in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields. Nano-silica is an inorganic chemical material, commonly known as white carbon black. It is cheap, amorphous white powder, non-toxic, odorless, and non-polluting. Its microstructure is spherical, with a flocculent and mesh quasi-particle structure, and is insoluble in water. Nano-silica is ultrafine nano-scale, with a size range of 1~100nm, so it has many unique properties and is widely used, such as improving the anti-aging, strength and chemical resistance of other materials. Although nanoparticles such as nano-silica have been widely used to improve the anti-aging, strength and chemical resistance of other materials, most of the current research focuses on improving the thermal and mechanical properties of cellulose acetate butyrate composites, and few studies have reported how to simultaneously improve the mechanical strength, ductility, UV blocking, antibacterial and ammonia-sensitive color change properties and functions of cellulose acetate butyrate. Therefore, how to simultaneously improve the mechanical strength, ductility, UV barrier, antioxidant, antibacterial and ammonia-sensitive color change properties and functions of cellulose acetate butyrate so that it can be used in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high-performance cellulose acetate butyrate composite material and a preparation method thereof. The high-performance cellulose acetate butyrate composite material has excellent mechanical strength, ductility, UV blocking, antioxidant, antibacterial and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, suitable for scaled-up production, and is suitable for food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields.

[0004] Technical solution of the present invention:

[0005] The present invention provides a high-performance cellulose acetate butyrate composite material, characterized in that it is composed of the following components in parts by weight: 100 parts of cellulose acetate butyrate, 5 parts of a plasticizer, and 2.5-10 parts of novel silicon dioxide hybrid nanoparticles;

[0006] The plasticizer is triethyl citrate;

[0007] The preparation method of the novel silicon dioxide hybrid nanoparticles comprises the following steps:

[0008] (1) Disperse 30 parts of nano-silicon dioxide in 2000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform silicon dioxide dispersion for later use;

[0009] (2) Take 14.01 parts of ferrous sulfate heptahydrate, add it to the silicon dioxide dispersion obtained in step (1), and stir at room temperature for 60 minutes to obtain a uniform mixed solution for later use;

[0010] (3) Take 4.05 parts of 4-hydroxycoumarin, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 min to obtain a uniform 4-hydroxycoumarin solution for later use;

[0011] (4) Add the 4-hydroxycoumarin solution obtained in step (3) to the mixed solution obtained in step (2), stir and react at room temperature for 20 min, then centrifuge, wash and dry in sequence to obtain novel silica hybrid nanoparticles.

[0012] The present invention also provides a method for preparing the above-mentioned high-performance cellulose acetate butyrate composite material, which is characterized by comprising the following steps:

[0013] (1) Add 100 parts of cellulose acetate butyrate and 5 parts of plasticizer to 2000 parts of ethanol, stir at 50°C for 20 minutes to obtain a uniform blend solution, cool to room temperature, and set aside;

[0014] (2) dispersing 2.5-10 parts of the novel silica hybrid nanoparticles in 500 parts of ethanol to obtain a uniform dispersion for later use;

[0015] (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at room temperature for 60 min to obtain a uniform film-forming solution for later use;

[0016] (4) The film-forming liquid obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a high-performance cellulose acetate butyrate composite material.

[0017] The application of the high-performance cellulose acetate butyrate composite material is characterized by being used in the fields of food packaging, smart materials, antibacterial materials, ultraviolet protection, ammonia detection, environmental monitoring and safety, etc.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The high-performance cellulose acetate butyrate composite material prepared by the present invention has excellent mechanical strength, ductility, UV blocking, anti-oxidation, antibacterial and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has wide application value in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope image of the novel silicon dioxide hybrid nanoparticles involved in the present invention;

[0021] Figure 2 These are actual photos of the cellulose acetate butyrate prepared in Comparative Example 1 and the high-performance cellulose acetate butyrate composite material samples prepared in Example. DETAILED DESCRIPTION

[0022] The present invention is described in detail below through examples. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the above content of the present invention. The parts of the raw materials are all parts by weight unless otherwise specified.

[0023] In the following specific embodiments and comparative example formulas and preparation methods, the cellulose acetate butyrate used is a product provided by Shanghai Yien Chemical Technology Co., Ltd. (CAS No.: 9004-36-8); the nano-silicon dioxide used is a product provided by Shanghai Aladdin Biochemical Technology Co., Ltd. (Article No.: S104596-100g, 99.5% metals basis, particle size of 30nm); 4-hydroxycoumarin used is an analytically pure reagent provided by Shanghai Yien Chemical Technology Co., Ltd.; triethyl citrate used is an analytically pure reagent provided by Shanghai Yuanye Biotechnology Co., Ltd., and ferrous sulfate heptahydrate is an analytically pure reagent provided by Xilong Scientific Co., Ltd.

[0024] In the following specific embodiments and comparative examples, the preparation method of the novel silicon dioxide hybrid nanoparticles comprises the following steps:

[0025] (1) Disperse 30 parts of nano-silicon dioxide in 2000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform silicon dioxide dispersion for later use;

[0026] (2) Take 14.01 parts of ferrous sulfate heptahydrate, add it to the silicon dioxide dispersion obtained in step (1), and stir at room temperature for 60 minutes to obtain a uniform mixed solution for later use;

[0027] (3) Take 4.05 parts of 4-hydroxycoumarin, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 min to obtain a uniform 4-hydroxycoumarin solution for later use;

[0028] (4) Add the 4-hydroxycoumarin solution obtained in step (3) to the mixed solution obtained in step (2), stir and react at room temperature for 20 min, then centrifuge, wash and dry in sequence to obtain novel silica hybrid nanoparticles.

[0029] Example 1

[0030] A high-performance cellulose acetate butyrate composite material is characterized by being composed of the following components in parts by weight: 100 parts of cellulose acetate butyrate, 5 parts of triethyl citrate, and 2.5 parts of novel silicon dioxide hybrid nanoparticles.

[0031] The preparation method comprises the following steps:

[0032] (1) Add 100 parts of cellulose acetate butyrate and 5 parts of triethyl citrate to 2000 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside;

[0033] (2) dispersing 2.5 parts of novel silica hybrid nanoparticles in 500 parts of ethanol to obtain a uniform dispersion for later use;

[0034] (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at room temperature for 60 min to obtain a uniform film-forming solution for later use;

[0035] (4) The film-forming liquid obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a high-performance cellulose acetate butyrate composite material.

[0036] Example 2

[0037] A high-performance cellulose acetate butyrate composite material is characterized by being composed of the following components in parts by weight: 100 parts of cellulose acetate butyrate, 5 parts of triethyl citrate, and 5 parts of novel silicon dioxide hybrid nanoparticles.

[0038] The preparation method comprises the following steps:

[0039] (1) Add 100 parts of cellulose acetate butyrate and 5 parts of triethyl citrate to 2000 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside;

[0040] (2) dispersing 5 parts of the novel silica hybrid nanoparticles in 500 parts of ethanol to obtain a uniform dispersion for later use;

[0041] (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at room temperature for 60 min to obtain a uniform film-forming solution for later use;

[0042] (4) The film-forming liquid obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a high-performance cellulose acetate butyrate composite material.

[0043] Example 3

[0044] A high-performance cellulose acetate butyrate composite material is characterized by being composed of the following components in parts by weight: 100 parts of cellulose acetate butyrate, 5 parts of triethyl citrate, and 10 parts of novel silicon dioxide hybrid nanoparticles.

[0045] The preparation method comprises the following steps:

[0046] (1) Add 100 parts of cellulose acetate butyrate and 5 parts of triethyl citrate to 2000 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside;

[0047] (2) dispersing 10 parts of the novel silica hybrid nanoparticles in 500 parts of ethanol to obtain a uniform dispersion for later use;

[0048] (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at room temperature for 60 min to obtain a uniform film-forming solution for later use;

[0049] (4) The film-forming liquid obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a high-performance cellulose acetate butyrate composite material.

[0050] Comparative Example

[0051] As a comparison standard of the above examples, the present invention provides a cellulose acetate butyrate material prepared without the novel silica hybrid nanoparticles, comprising the following steps:

[0052] (1) Add 100 parts of cellulose acetate butyrate and 5 parts of triethyl citrate to 2000 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside;

[0053] (2) Add 500 parts of ethanol to the blended solution obtained in step (1), and stir at room temperature for 60 min to obtain a uniform film-forming solution for later use;

[0054] (3) The film-forming solution obtained in step (2) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a cellulose acetate butyrate material.

[0055] Structure and performance test:

[0056] The cellulose acetate butyrate material prepared in the above comparative example and the high-performance cellulose acetate butyrate composite material prepared in the example were subjected to performance tests, wherein the UV-visible properties were tested by a UV-visible spectrometer, and the average UV transmittance was calculated with reference to GB / T 18830-2009; the tensile properties were tested by an electronic tensile testing machine (LDW-2G); the antibacterial property of the material was tested in accordance with QBT2591 2003; the ammonia response test method was as follows: the sample material was exposed to an ammonia environment for 5 minutes, the color change of the sample material was observed and recorded, and the color difference value ∆E of the sample material before and after the ammonia response was calculated (Note: ∆E >3 indicates an obvious color change visible to the human eye).

[0057] The DPPH free radical scavenging experimental method is as follows: In the experimental group, 0.2 g of the sample material was cut into pieces and soaked in 5 mL of ethanol. After soaking for 24 h, 2 mL of the supernatant of the soaking solution was extracted and set aside; then, 1 mL of 50 mg / L DPPH solution was added to the 2 mL of supernatant, and the mixture was shaken and placed in the dark at room temperature for 1 h; then, the absorbance of the mixture at 517 nm (denoted as A) was tested using an ultraviolet spectrophotometer. sample ); for the control group, 1 mL of 50 mg / L DPPH solution was added to 2 mL of ethanol, and the mixture was shaken and placed in the dark at room temperature for 1 h; then, the absorbance of the mixture at 517 nm (denoted as A) was measured by a UV spectrophotometer. control );DPPH free radical scavenging rate (%)=100*(A control -A sample ) / A control .

[0058] The above performance test data is shown in Table 1.

[0059] Table 1 Sample performance test data

[0060]

[0061] The results of the ammonia response test experiment show that the cellulose acetate butyrate material prepared in the comparative example is colorless and transparent. After being exposed to an ammonia environment for 5 minutes, its color does not change, and it still exhibits colorless and transparent optical properties, and its ∆E value is 0.59 (that is, the color difference is negligible and cannot be distinguished by the human eye). The high-performance cellulose acetate butyrate composite materials prepared in Examples 1, 2 and 3 can all undergo significant color changes after being exposed to an ammonia environment for 5 minutes. In particular, the high-performance cellulose acetate butyrate composite material prepared in Example 3 is light yellow, and after being exposed to an ammonia environment for 5 minutes, its color changes significantly (from light yellow to brown), and its ∆E value is as high as 35.52 (Note: ∆E >3 indicates a significant color change visible to the human eye).

[0062] The results of the antibacterial test show that the cellulose acetate butyrate material prepared in the comparative example does not show obvious antibacterial activity against Escherichia coli and Staphylococcus aureus, while the high-performance cellulose acetate butyrate composite material prepared in Example 3 has an antibacterial rate of more than 99% against Escherichia coli and Staphylococcus aureus, that is, the high-performance cellulose acetate butyrate composite material prepared in the example has excellent antibacterial activity.

[0063] The results of the DPPH free radical scavenging experiment show that the cellulose acetate butyrate material prepared in the comparative example has no obvious antioxidant activity, while the high-performance cellulose acetate butyrate composite material prepared in Example 3 has a DPPH free radical scavenging rate of 87.9%, that is, the high-performance cellulose acetate butyrate composite material prepared in the example has excellent antioxidant activity.

[0064] In summary, it can be seen from the sample performance test data (see Table 1) that the high-performance cellulose acetate butyrate composite material prepared by the present invention has excellent mechanical strength, tensile elongation at break (i.e. ductility), UV blocking, antioxidant, antibacterial and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has wide application value in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields.

[0065] The content of the present invention is not limited to the embodiments listed, and any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the description of the present invention are covered by the claims of the present invention.

Claims

1. A high-performance cellulose acetate butyrate composite material, characterized in that: The invention is composed of the following components in parts by weight: 100 parts of cellulose acetate butyrate, 5 parts of plasticizer, and 2.5-10 parts of novel silicon dioxide hybrid nanoparticles; The plasticizer is triethyl citrate; The preparation method of the novel silicon dioxide hybrid nanoparticles comprises the following steps: (1) Disperse 30 parts of nano-silicon dioxide in 2000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform silicon dioxide dispersion for later use; (2) Take 14.01 parts of ferrous sulfate heptahydrate, add it to the silicon dioxide dispersion obtained in step (1), and stir at room temperature for 60 minutes to obtain a uniform mixed solution for later use; (3) Take 4.05 parts of 4-hydroxycoumarin, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 min to obtain a uniform 4-hydroxycoumarin solution for later use; (4) The 4-hydroxycoumarin solution obtained in step (3) is added to the mixed solution obtained in step (2), and the mixture is stirred at room temperature for 20 min. The mixture is then centrifuged, washed, and dried to obtain novel silica hybrid nanoparticles.

2. The method for preparing a high-performance cellulose acetate butyrate composite material according to claim 1, characterized in that The steps include: (1) Add 100 parts of cellulose acetate butyrate and 5 parts of plasticizer to 2000 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside; (2) dispersing 2.5-10 parts of the novel silica hybrid nanoparticles in 500 parts of ethanol to obtain a uniform dispersion for later use; (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at room temperature for 60 min to obtain a uniform film-forming solution for later use; (4) The film-forming liquid obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a high-performance cellulose acetate butyrate composite material.

3. The use of a high-performance cellulose acetate butyrate composite material according to claim 1, characterized in that: Used in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety fields.